2022
DOI: 10.2106/jbjs.21.01436
|View full text |Cite
|
Sign up to set email alerts
|

Patients Who Undergo Rotator Cuff Repair Can Safely Return to Driving at 2 Weeks Postoperatively

Abstract: Background:Evidence-based guidelines are lacking for return to driving following rotator cuff repair (RCR). As a result, surgeons are often overly conservative in their recommendations, placing potential undue burden on patients and their families. Therefore, the primary objective of this study was to formulate evidence-based return-to-driving guidelines.Methods:Thirty-two subjects planning to undergo primary RCR were enrolled. Driving fitness was assessed in a naturalistic setting with an instrumented vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…( 60 ), Hasan et al . ( 62 ), Badger et al ( 63 ), McClelland et al . ( 64 ), Newington et al ( 65 ), Hammert et al ( 66 ), Acharya et al .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…( 60 ), Hasan et al . ( 62 ), Badger et al ( 63 ), McClelland et al . ( 64 ), Newington et al ( 65 ), Hammert et al ( 66 ), Acharya et al .…”
Section: Resultsmentioning
confidence: 98%
“…In total, 68 studies were identified meeting our study aims and inclusion criteria for both upper and lower extremity procedures ( Fig. 1 , Table 1 , Supplementary Tables 1 and 2) ( 1 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ). There was a wide variation in procedures performed and sample size, the study methodology, and measurements obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many surgeons guess or estimate a duration, but laudably a team from Roanoke (Virginia, USA) have attempted to objectively answer the question and develop evidence-based guidelines. 4 In their study, 32 patients undergoing a primary repair of the rotator cuff were studied prospectively, and driving fitness was assessed in a naturalistic setting in an instrumented vehicle on public roads with safety monitoring on board. Specific driving tasks and manoeuvres were monitored and evaluated, including turning, parking, and U-turns.…”
Section: Patients Who Undergo Rotator Cuff Repair Can Safely Return T...mentioning
confidence: 99%